Stabilitas Fenomena the Monday Effect di Bursa Efek Jakarta - Hambayanti, Septi; Budileksmana, Antariksa (Universitas Muhammadiyah Yogyakarta, Indonesia, 2006)
The Monday Effect phenomenon is a seasonal anomaly in financial markets, which occurs when the return on stock markets is significantly negative on Monday. The presence of this anomaly violates the weak form of market efficiency because stock returns are not random, but are predictable based on certain calendar effects. The objective of this study is to empirically re-examine the presence of the Monday Effect phenomenon and the stability of the presence of this phenomenon. The sample used in this study are stock market index at Jakarta Stock Exchange (JSX), which IHSG index and LQ-45 index, over 1999 to 2005, as the proxy. The major conclusion of this study is that Monday returns are significantly negative and are lower than returns during the rest of the week at Jakarta Stock Exchange (JSX), both in IHSG index as well as LQ45 index. We also confirm the evidence over the 1999-2005 observation that: (1) the Monday Effect phenomenon at JSX, both in IHSG index and LQ45 index as well, are unstable and significantly time-varying, and (2) the intensity of the Monday Effect phenomenon at JSX, both in IHSG index as well as LQ45 index, tend to decrease since 2000, Â and even disappeared in 2005.